CHIAPPINI, L.; MARTINS, M. H.; PESAVENTO, S. J. (Orgs.) Pampa e Cultura: de Fierro a Netto. - Kahman, Andrea Cristiane (Organon, 2004)
CHIAPPINI, L.; MARTINS, M. H.; PESAVENTO, S. J. (Orgs.) Pampa e Cultura: de Fierro a Netto. PortoAlegre: Editora da UFRGS / Instituto Estadual do Livro, 2004. 285p.Resenhado por: Andrea Cristiane Kahmann